Formación De Formadores Y Mediadores Escolares Con Análisis Transaccional - López, Mabel Claudia (European Scientific Journal, ESJ, 2016)
The United Nations, particularly through UNESCO, UNICEF and WHO, have been dealing with school violence. In Argentina, in the recent years proactive and preventive programs have been generated, including School Mediation, where students act as mediators at the onset of problems that generate violence, with previous preparation with specialized teachers to fulfill that role. On this basis we presented a pilot program to achieve the handling of specific techniques for student trainers of school mediators, about Effective Communication applying the following instruments of Transactional Analysis: Personality model (PAN: Parent-Adult-Child), behavior signs, transactions, strokes, existential positions and emotions. All this allows the recognition of non-conscious behaviors and settlement of change goals for a better school coexistence.